2007
DOI: 10.1038/sj.bmt.1705849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prior rituximab on high-dose therapy and autologous stem cell transplantation in follicular lymphoma

Abstract: Autologous stem-cell transplantation (ASCT) has been used in follicular lymphoma (FL) to achieve durable responses in first remission or in the relapsed or refractory settings. Addition of rituximab to chemotherapy for FL has been shown to improve survival. The impact of prior therapy with rituximab upon the effectiveness of high-dose therapy (HDT) and ASCT in patients with FL is unknown. We retrospectively reviewed consecutive patients with FL who underwent HDT and ASCT. Patients were categorized according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Post-transplant 3-year OS were similar in both groups[14]. Kang et al also showed similar OS post-ASCT in patients who had (N=35) or had not (N=71) received rituximab prior to transplant[16]. However, in our study, the difference in OS (and PFS) became clear once we separated the RS from RR patients.…”
Section: Resultssupporting
confidence: 45%
“…Post-transplant 3-year OS were similar in both groups[14]. Kang et al also showed similar OS post-ASCT in patients who had (N=35) or had not (N=71) received rituximab prior to transplant[16]. However, in our study, the difference in OS (and PFS) became clear once we separated the RS from RR patients.…”
Section: Resultssupporting
confidence: 45%
“…Two retrospective studies [52,53] analyzed the outcomes of patients treated with autologous HSCT or chemotherapy or chemoimmunotherapy in patients progressed or relapsed FL. Other cohorts assessed the role of autologous HSCT in rituximab pretreated patients [37,[54][55][56][57][58][59]. The efficacy of rituximab prior to stem cell collection as in vivo purging has been tested by a randomized trial [60].…”
Section: Issue 4: Assessment Of Response (Consensus-based Recommendatmentioning
confidence: 99%
“…3 While management strategies have changed, advanced-stage FL remains an incurable disease using conventional therapies. 4 Approximately 85% of FL is associated with a specific balanced translocation, t(14;18)(q32;q21), that leads to overexpression of the antiapoptotic gene BCL2 due to its relocation in proximity to an IgH enhancer element. [5][6][7][8] This genetic abnormality alone, however, is unlikely to produce clinical FL, as BCL2-overexpressing transgenic mice do not develop lymphoma 9,10 and t(14;18)-bearing lymphocytes have been frequently demonstrated in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%